ANALISIS FAKTOR PENERIMAAN MASYARAKAT TERHADAP VAKSIN COVID-19 DI KOTA TEBING TINGGI SELAMA PANDEMI COVID-19 - Ashar, Yulia Khairina; Sari, Ananda Dwi Puspita; Ananda, Dwika; Utari, Kania (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2023)
The widespread misconceptions and hoaxes regarding the Covid-19 vaccine are the driving cause for public uncertainty, producing public doubt and resulting in low availability and public confidence in the Covid-19 vaccine. The purposeÂ of this research was to see if there was a link between the characteristics of the community and the availability of vaccines.Â The population in this study was the entire populationÂ persiakan, in Tebing TinggiÂ city with a population of 7,238 people. This study’s sample was drawn from the general community and met the inclusion requirements, yielding a sample of 100 people. A cross-sectional study was used in the investigation. The data was analyzed using univariate and bivariate techniques, with statistical analysis utilizing the chi-square test (P-value 0.05). According to the study’s findings, 51% of respondents are willing to receive the Covid-19 vaccination. Factors that influence the Tebing Tinggi community’s willingness to participate Age, gender, marital status, education, work, economic conditions, and public faith in the COVID-19. Vaccine are all factors that influence vaccination rates. Respondents came to the conclusion that public confidence in the Tebing Tinggi vaccination is 41%. Meanwhile, the Tebing Tinggi community has expressed a 51 percent desire to get the COVID-19 vaccine. Suggestions for the Tebing Tinggi local government and the Health Office in terms of vaccine distribution. Â KeywordsÂ Â Â Â Â Â Â Â : Acceptance, Covid-19, Vaccines